The Politics of Children's Rights and Representation - Sandin, Bengt; Josefsson, Jonathan; Hanson, Karl; Balagopalan, Sarada (Studies in Childhood and Youth, 2023)
This open access edited volume investigates children and youth's deep entanglement in today's major global, national, and local transformations and processes: wherein they are not mere spectators and objects of transformations but instead actively shape them through various social, economic, and political representations. International contributions illuminate the problems that arise when children's rights and participation become a site of contestation and power over who represents whom, what, when, and where. The authors do not provide simple solutions, instead offering an understanding of the fundamental nature of these problems as founded in the application of rights and the nature of representation in modern society. Together, the authors emphasize that child representation must take into account the local and spatial context of how representations of children are discussed, as well as possible discrepancies between local, regional, national, and global processes.